Արմենոցիդի հետևանքների վերացման հրամայականը. պատմաքաղաքական դասերը, Արցախյան Պատերազմի հաջողված փորձը Մհեր Հարությունյան - Հարությունյան, Մհեր (ԱրՊՀ հրատ․)
На протяжении ста лет армянский народ требует восстановления исторической справедливости. Обобщение и переосмысление многовекового опыта очень важно для нашего народа, тем более сейчас, накануне 100-летия Геноцида армянского народа. Только таким путем можно найти ответы на актуальные вопросы современности. Геноцид - не только историческая память нашего народа, но и фактор, влияющий на настоящее и определяющий ее будущее. Продолжая проводимую Турцией политику арменоцида, Азербайджан с 1918 года, осуществляет в Восточной Армении политику этнических чисток и геноцида армянского населения. Отразив военную агрессию Азербайджана, армянский народ не только защитил неотъемлемое право жить на родной земле, но и освободил часть исконно армянских земель, захваченных азербайджано-турецкими агрессорами в 1918-1920 годах. И это единственно правильный путь, направленный на ликвидацию последствий политики арменоцида и достижение сверхцели – стать хозяевами своей страны. The Armenian people have been demanding to restore the historical justice for a hundred years. On the eve of the Armenian Genocide 100th centenary it has become particularly important for our people to sum up the centuries-long experience and to ponder it over. Only that way we can find the solutions for the most actual issues of present day. The Armenian Genocide is not only the historical memory of our nation but it is also a mighty factor which affects our present and determines our future. Being the successor of the Armenocide policy of Turkey, Azerbaijan has been carrying out the programs of the ethnical cleansing and genocide of the Armenian population since 1918. Resisting the military aggression of Azerbaijan the Armenian people not only defended their ultimate right to live on their native land but also liberated part of the historical Armenian territories which were occupied by Azeri-Turkish forces from 1918-1920. Only defense and resistance can make it possible to liquidate the consequences of the Armenocide and to reach the all-Armenian supreme goal-that is to become the master of our own land, our motherland.
Keywords: Արցախ; Հայոց ցեղասպանություն